0833 Midlife Sleep Health is Associated With Later-Life Depression and Anxiety. (27th May 2020) - Hagen, E W; Barnet, J H; Sprecher, K E; Peppard, P E
Abstract: Introduction: Several aspects of sleep - collectively conceptualized as 'sleep health' - are associated with anxiety and depression. This study investigated whether specific components of sleep health experienced during midlife are associated with depression and anxiety symptoms in later life. Methods: A subset of Wisconsin Sleep Cohort participants (n=616; 45% female; mean [SD] baseline age=55 [8] years) completed 4 study visits at 4-year intervals. Visits included polysomnography and questionnaires about sleep, mood, and health. Outcomes (Zung depression score, State and Trait Anxiety) were regressed on sleep health characteristics (AHI, %N3 sleep, %REM sleep, sleep efficiency, sleep latency, sleep duration, sleep debt, nap duration, insomnia symptoms, circadian preference, excessive daytime sleepiness [EDS], Epworth Sleepiness Scale [ESS]) using 2 types of linear models adjusting for age, sex, BMI, education, exercise, smoking, and caffeine consumption: 1) longitudinal models in which baseline sleep health predicted mood outcomes 12 years later (adjusting for baseline levels of the outcome variable), and 2) models in which 12-year change in sleep health predicted 12-year change in outcomes. Results: Longer nap duration, evening circadian preference, and EDS during midlife were associated with worse depression scores in later life. 12-year increases in nap duration, EDS, and ESS were associated with 12-year worsening of depression. Longer sleep duration and greater EDS during midlife were associated with worse trait anxiety in later life. 12-year increases in sleep duration, nap duration, insomnia symptoms, EDS and ESS were associated with 12-year worsening of trait anxiety. Greater AHI and EDS during midlife were associated with worse state anxiety in later life. 12-year increases in ESS were associated with worsening state anxiety. (P<0.05 for all reported results.) Conclusion: Multiple aspects of sleep health experienced during midlife are associated with greater depression and anxiety in later life. Support: NIH grants: National Institutes of Aging (R01AG058680; R01AG036838); National Heart, Lung, and Blood Institute (R01HL62252); National Center for Research Resources (1UL1RR025011)